Environmental Friendliness of a Person’s Musical Space as a Factor of Personality Disharmony Prevention - Maksymova, Nataliia Yu.; Hrys, Antonina; Pavliuk, Mariia M.; Maksymov, Mykola V.; Ivantsev, Nataliia I. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
The article discusses correlations between a person’s musical space and the degree of personality harmony. The sound environment of a person always influences personality formation and his/her behaviour. By studying a person’s musical preferences, a degree of harmony of his/her personality development can be understood. The article’s purpose is to determine the correlation of musical preferences with the existence of personality disharmony and types of his/her relationships with others, as well as to determine the specifics of the impact of music on personality features of people with special needs. The authors started from the assumption that, depending on his/her personality traits, a person prefers certain patterns of musical discourse. The empirical study aimed to study relations of such personality features that testify the personality disharmony and are manifested in non-viable relationships with others. The personality manifestations in communications and educational activities were also analyzed. It was determined that music therapy plays an important role in the formation of their personalities for people with special needs. The correlation of personality traits with the perception of music has shown that persons with the external locus of control choose musical discourses that, as for their psychological content, reflect uncertainty, amorphy of world perception or its simplicity, primitiveness; on the contrary, persons with the internal locus of control choose energetic, purposeful music. Persons with the disharmonious type of relationships choose music whose psychological and emotional content reflects the next personality traits: possible aggressive behaviour; a life course that does not demand serious decisions, irresponsibility, and reluctance to resolve complex situations.